Nonapoptotic role of caspase‐3 in regulating Rho1GTPase‐mediated morphogenesis of epithelial tubes of Drosophila renal system. Issue 5 (24th November 2021) - Ojha, Shainy; Tapadia, Madhu G.
Abstract: Background: Cells trigger caspase‐mediated apoptosis to eliminate themselves from the system when tissue needs to be sculptured, or they detect any abnormality within them, thus preventing irreparable damage to the host. However, nonapoptotic activities of caspases are also involved in many cellular functions. Interestingly, Drosophila Malpighian tubules (MTs) express apoptotic proteins, without succumbing to cell death. Results: We show apoptosis‐independent role of executioner caspase‐3, Drice, in MT morphogenesis. Drice is required for precise cytoskeleton organization and convergent extension, failing which morphology, size, cell number, and arrangement get affected. Furthermore, characteristic stellate cell shape transformation in MTs is also governed by Drice. Genetic interaction study shows that Drice mediates its action by regulating Rho1GTPase functionally, and localization of polarity protein Disc large. Subsequently, downregulation of Rho1GTPase in Drice mutants significantly rescues the cystic MTs phenotype. The study shows a mechanism by which Drice governs tubulogenesis via Rho1GTPase‐mediated coordinated organization of actin cytoskeleton and membrane stabilization. Conclusion: Collectively our findings suggest a nonapoptotic function of caspase‐3 in fine‐tuning of cellular rearrangement during tubule development, and these results will add to the growing understanding of diverse roles of caspases during its evolution in metazoans. Key Findings: Collectively our findings suggest a non‐apoptotic function of caspase‐3 in the fine tuning of cellular rearrangement during tubule development, and these results will add to the growing understanding of diverse roles of caspases during its evolution in metazoans.